2003
DOI: 10.1021/ma021799x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Hyperbranched Poly(ether ketone)s Derived from 3,5-Bis(4-fluorobenzoyl)phenol

Abstract: Bis(4-fluorobenzoyl)phenol was polycondensed under various reaction conditions. Low molecular weights were obtained (Mn < 8000 Da), and MALDI-TOF mass spectrometry indicated that the chain growth was limited by cyclization. In the best mass spectra the cyclic, hyperbranched poly-(ether ketone)s were detectable up to masses around 14 000 Da. When 4,4′-difluordiphenyl sulfone was added, star-shaped polymers having a diphenyl sulfone star center were formed, but cyclization was not completely suppressed. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…However, with one exception, 47 the extent of cyclization was not studied by other research groups. A reinvestigation of polycondensations based on 3,5-bis(4-fluorobenzoyl) phenol (Scheme 9) performed by the authors 48 yielded a product almost completely consisting of hyperbranched poly(ether ketone)s having a cyclic core.…”
Section: Figure 1 Number Fraction Of Rings (N R ) Versus Conversion (P)mentioning
confidence: 99%
“…However, with one exception, 47 the extent of cyclization was not studied by other research groups. A reinvestigation of polycondensations based on 3,5-bis(4-fluorobenzoyl) phenol (Scheme 9) performed by the authors 48 yielded a product almost completely consisting of hyperbranched poly(ether ketone)s having a cyclic core.…”
Section: Figure 1 Number Fraction Of Rings (N R ) Versus Conversion (P)mentioning
confidence: 99%
“…In contrast to Flory's cascade theory [3,4] and in contrast to a report of Chu et al [57] it has been recently demonstrated for various ''ab n '' polycondensations that cyclization competes with chain growth. [58][59][60][61][62][63] Cyclization has the consequence that molecules with a cyclic core and hyperbranched ''star-arms'' are formed (Scheme 4). Since cyclization consumes the only ''a''-function in a hyperbranched molecule, it limits the average molar mass (M n ) of a sample according to Equation (2) quite analogous to two-dimensional polycondensations.…”
Section: Polycondensation Of ''Ab N '' Monomersmentioning
confidence: 99%
“…Gooden et al [62] reported for polycondensations of the monomers 1 and 2 (Scheme 5) that up to 60 mol% of the polycondensates from 1 possess a cyclic core, and up to 90% of the polymer derived from 2. Polycondensations of monomers 3a and 3b were studied by Kricheldorf et al [63] and the reaction conditions were optimized for a clean polycondensation with maximum conversion. A hyperbranched poly(ether ketone) was obtained.…”
Section: H R Kricheldorfmentioning
confidence: 99%
“…None-the-less, these results disagree with Flory's cascade theory, and support the polycondensation theory of the author. More recently, Kricheldorf et al [108] reinvestigated polycondensations of the 3,5-bisfluorobenzoyl phenol (53) and its trimethylsilyl derivative with regard to the formation of cycles (polycondensations of 49a were first described by Miller et al [109] ). Sulfolane as reaction medium yielded particularly clean polycondensations with high conversions.…”
Section: Syntheses Of Hyperbranched and Star-shaped Polymersmentioning
confidence: 99%